Formal Error Rate in a Computerized Obstetric Medical Record - Jelovsek, F.; Hammond, W. (Methods of Information in Medicine, 1978)
Missing and incompatible data rates in a computerized obstetric medical record are described and range from 0-84% with a median of 6%. Comparison is made to previous manual records and missing data rates appear to be similar. Certain unique characteristics of each variable checked (logistical problems, data sheet format, and low frequency, expected positive response) seem to have a stronger influence on the missing rate than do categories of time collected, source, type and transmission mode. There is bias in missing rates according to different patient types, but incompatible data rates appear not to be influenced.
Keywords: Medical Record System; Obstetrics; Data Error Rate; Missing Data